The Element Of State Financial Losses In Corruption Offenses In The Process Of Procuring Sugarcane Seeds (Case Study on Case No. 100 / Pid.Sus-TPK / 2017 / PN.Smg) - Rustanto Rustanto (Jurnal Daulat Hukum, 2019)
This study aims to analyze how to prove the element of state financial losses in corruption offenses in the process of procuring sugarcane seeds in accordance with case No. 100 / Pid.Sus-TPK / 2017 / PN.Smg. The method used is sociological juridical approach techniques with the data collection through interviews and library studies. Then the data obtained were analyzed using descriptive normative. The results of the study indicate that the method of calculating BPK auditors through three stages of verification items, namely the realization of payments from the State financial post, the realization of procurement of sugarcane seeds that can be accounted for and calculating State financial losses from the previous stage difference. This corruption crime has proven to be detrimental to the State's finance of Rp. 2,038,616,969.00. Keywords: Authentication; Loss; Corruption.